Aiming Beyond: A Pharmacist Impact on 90-Day Readmissions and Clinical Outcomes Within a Family Medicine Service. (December 2020) - Wiegmann, Lindsey E.; Belisle, Matthew S.; Alvarez, Kristin S.; Kale, Neelima J.
Previous studies have shown pharmacists positively impact 30-day readmission rates. However, there is limited data regarding the effect of clinical pharmacist (CP) follow-up on 90-day readmission or evaluation of disease-specific goals after hospitalization. Investigators analyzed the impact of postdischarge extended CP follow-up within a family medicine service (FMS). The primary end point was all-cause 90-day readmission rates. Secondary end points included all-cause 30- and 60-day readmission rates and the achievement of disease-specific goals postdischarge. Retrospective chart review was performed for patients admitted from August 2016 to November 2017 who were seen by a physician within the FMS 14 days postdischarge. Fourteen percent of patients within the CP intervention group were readmitted within 90 days in comparison to 22% in the standard of care group ( P = .244). Readmission rates at 30 and 60 days were as follows: intervention group 2%, 10%, and standard of care group 16%, 22% ( P = .015, P = .089, respectively). In addition, multiple patients with uncontrolled diabetes who completed CP visits upon hospital discharge met glycemic goals at the end of the study time period. Despite inclusion of the CP in postdischarge care, 90-day readmission rate remained unchanged.